Structural description of humic substances from subtropical coastal environments using elemental analysis, FT-IR and 13C-solid state NMR data - Sierra, M. M.D.; Giovanela, M.; Parlanti, E.; Esteves, V. I.; Duarte, A. C.; Fransozo, A. [UNESP]; Soriano-Sierra, E. J. (My University, 2005)
Elemental composition and spectroscopic properties (FT-IR and CP/MAS 13C-NMR) of sedimentary humic substances (HS) from aquatic subtropical environments (a lake, an estuary and two marine sites) are investigated. Humic acids (HA) are relatively richer in nitrogen and in aliphatic chains than fulvic acids (FA) from the same sediments. Conversely, FA are richer in carboxylic groups and in ring polysaccharides than HA. Nitrogen is mostly present as amide groups and for lake and marine HS the FT-IR peaks around 1640 cm-1 and 1540 cm-1 identify polypeptides. Estuarine HS exhibit mixed continental-marine influences, these being highly influenced by site location. Overall, the data suggest that aquatic and mixed HS are more aliphatic than has been proposed in current models and also that amide linkages form an important part of their structural configuration.
Keywords: Coastal marine; Estuary; Fulvic acids; Humic acids; Infrared spectroscopy; Lake